The Implementation of Monopins Learning Media to Improve Student Learning Outcomes in Science and Technology Classes for Grade IV Students of Elementary School 1 Kalampangan - Hidayanti, Erni Wahyu; Rizal, Setria Utama; Mahmudah, Istiyati (Jurusan Pendidikan Guru Madrasah Ibtidaiyah, 2024)
This study stems from the fact that there are still many students in class IV-A SDN-1 Kalampangan who have not been able to exceed the criteria for achieving learning objectives. Based on the results of tests conducted at the time of pre-research, only 25% of students achieved the criteria for achieving learning objectives. Therefore, this study aims to 1) Describe the implementation of learning by using smart monopoly (monopin) learning media in the subject of IPAS force material around us in class IV A students of SDN 1 Kalampangan, 2) Improve learning outcomes of IPAS subject matter of forces around us through monopin learning media in class IV A students of SDN 1 Kalampangan. This study uses a classroom action research method (PTK) with the Kemmis & McTaggart model which includes four steps, namely planning, implementation, observation, and reflection. The research subjects consisted of IV-A homeroom teacher and 16 students. Data collection in this study used instruments including observation using observation sheets, interviews using interview guidelines, tests, and documentation. The results showed that 1) Learning by using monopin learning media can create an effective and fun learning atmosphere, besides that student learning outcomes have increased, 2) At the pre-cycle stage, the number of students who were complete was 4 people (25%) and those who were not coumplete were 12 people (75%). Cycle I, out of 16 students who were complete as many as 11 students (68.75%) and those who were not complete were 3 students (31.25%). Whereas in Cycle II, there were 14 students (87.50%) who were complete and 2 students (12.50%) who were not complete.